Pengaruh PAD, DAK, dan DAU Terhadap Perilaku Oportunistik Penyusun Anggaran pada Pemerintah Provinsi Sumatera - Aura Putri Syahrani; Eka Jumarni Fithri; Kartika Rachma Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to examine the effect of Regional Original Revenue (PAD), Special Allocation Funds (DAK), and General Allocation Funds (DAU) on the Opportunistic Behavior of Budget Preparer in Provincial Governments in Sumatra in 2018-2022. The data used in this research is panel data from 10 Provinces in Sumatra in year 2018 up to year 2022. This research utilizes secondary data in the form of LRA (Budget Realization Report) of the Provincial Government obtained from the BPK RI website and expenditure data based on functions obtained from the DJPK website. The analysis method used is panel data regression analysis using the Eviews 12 program. The results of this study show that partially Regional Original Revenue (PAD) and Special Allocation Funds (DAK) have an influence on the Opportunistic Behavior of Budget Preparer in Provincial Governments in Sumatra, while General Allocation Funds (DAU) partially have no influence on the Opportunistic Behavior of Budget Preparer in Provincial Governments in Sumatra. Regional Original Revenue (PAD), Special Allocation Funds (DAK), and General Allocation Funds (DAU) simultaneously have an influence on the Opportunistic Behavior of Budget Preparer in Provincial Governments in Sumatra.